The Theology Of The Incarnation: A Paradigm For A Theology Of Contextual In The Era Of The Third Millennium - Ranto Ranto (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2021)
Why is it necessary to learn the Theology of the Incarnation, it is not separated from some of the advantages of basic and very critical of the approach of this theology. First, the Theology of the Incarnation to take the role as a theology of contextual provided the Bible itself, and that God has taken this pattern in the states themselves, and his word to man. This is the pattern and the case of biblical theology and contextual theology in the context of health. Next, as an example the case of theology is contextual, the role of the incarnation embodies well the demands of the two mandates the basis of theology is contextual. In this case, God and His Word are eternal it is final, eternal, and unchangeable in the encounter, and ‘incarnation” in humanity and human culture. While at the same time, there is no doubt that it is relevant and following the bible.